Treatment of digestate residues for energy recovery and biochar production: From lab to pilot-scale verification. (20th August 2020) - Li, Chunxing; Li, Jie; Pan, Lanjia; Zhu, Xinyu; Xie, Shengyu; Yu, Guangwei; Wang, Yin; Pan, Xiaofang; Zhu, Gefu; Angelidaki, Irini
Abstract: Hydrothermal pretreatment was used for dewatering food waste digestate residue, and biochar/biogas were generated from the separated solid and liquid phases via pyrolysis and anaerobic digestion, respectively. Increasing hydrothermal pretreatment temperature (110–200 °C) clearly improved dewaterability, whereas enhancing treatment duration (30–90 min) had little impact. The optimal condition of 160 °C/30 min gave the best dewatering performance with relative lower energy consumption and was chosen for pilot-scale verification achieving 61.7 wt% dry weight content after mechanical squeezing. Moreover, the filtrate and filter cake obtained at optimal condition were applied for biogas and biochar production in lab scale. The methane yield of the filtrate was 335 mL/g COD. Pyrolysis temperature of 500 °C gave better biochar performance and was verified in a pilot scale test. Additionally, the heavy metals in digestate were effectively immobilized during hydrothermal dewatering and pyrolysis processes. In the end, mass/energy balance calculated using pilot-scale data presented the combined systems provided a promising strategy for accomplishing energy recovery and resource reuse of digestate residue. Graphical abstract: Image 1 Highlights: HTPT, pyrolysis and anaerobic digestion were used for DR treatment. °C and 500 °C performed better performances in DR dewatering and biochar production. The optimal conditions were successfully verified at pilot-scale tests. Mass/energy balance showed slight energy deficit of the whole process. t biochar was produced from 100 t DR.